2015
DOI: 10.1038/ncomms7273
|View full text |Cite
|
Sign up to set email alerts
|

Indole is an essential herbivore-induced volatile priming signal in maize

Abstract: Herbivore-induced volatile organic compounds prime non-attacked plant tissues to respond more strongly to subsequent attacks. However, the key volatiles that trigger this primed state remain largely unidentified. In maize, the release of the aromatic compound indole is herbivore-specific and occurs earlier than other induced responses. We therefore hypothesized that indole may be involved in airborne priming. Using indole-deficient mutants and synthetic indole dispensers, we show that herbivore-induced indole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
396
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 363 publications
(410 citation statements)
references
References 62 publications
13
396
0
1
Order By: Relevance
“…Bx2 encodes a cytochrome P450 that uses indole as a substrate to produce indolin-3-one (Frey et al, 1997) and is thus the committing enzyme for benzoxazinoid biosynthesis. Since a bx2 mutation is less likely to affect the production of other indole-derived plant defensive metabolites (Erb et al, 2015), the improved aphid growth on this mutant line is more plausibly caused by reduced benzoxazinoid content.…”
Section: Discussionmentioning
confidence: 99%
“…Bx2 encodes a cytochrome P450 that uses indole as a substrate to produce indolin-3-one (Frey et al, 1997) and is thus the committing enzyme for benzoxazinoid biosynthesis. Since a bx2 mutation is less likely to affect the production of other indole-derived plant defensive metabolites (Erb et al, 2015), the improved aphid growth on this mutant line is more plausibly caused by reduced benzoxazinoid content.…”
Section: Discussionmentioning
confidence: 99%
“…Niinemets et al (2013) found evidence that quantitative relationships exist between the severity of biotic stress and induced volatile emissions, in addition to the previously demonstrated dose-response relationships for abiotic stresses. Erb et al (2015) showed that herbivore induced indole emissions in maize plants precede the release of mono-, homo-, and sesquiterpenes, supporting the conclusion that indole is involved in the airborne priming of terpenoids. Different plant stress mechanisms typically elicit release of the same ubiquitous stress volatiles, such as indole, and more stress-specific mono-and sesquiterpene blends (Erb et al, 2015;Gentner et al, 2014;Niinemets et al, 2013;Schmelz et al, 2003).…”
Section: Introductionmentioning
confidence: 48%
“…Such compounds can also be emitted by vegetation; for example, indole is produced by wide variety of plants (Cardoza et al, 2003;De Boer et al, 2004;Gols et al, 1999;McCall et al, 1993;Turlings et al, 1990;. Indole is emitted in response to physical or herbivore-induced stress (Erb et al, 2015;Frey et al, 2004;Misztal et al, 2015;Niinemets et al, 2013;Schmelz et al, 2003;Turlings et al, 2004) and during flowering events (Gentner et al, 2014). Once emitted, indole performs critical roles in plant ecology, for example in attracting pollinators (Zito et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cucumbers, we found one difference between Si+ and Si-plants in production of volatiles, an increase in Indole. Although, our volatile extraction was conducted on harvested plants that had not experienced herbivory, while the Kvedaras et al (2010) study used plants that were currently undergoing herbivore damage, the constitutive increase in Indole indicates that Si+ plants are more primed for herbivore defense, and able to communicate attack to surrounding plants (Erb et al 2015). This, along with the potential greater sensitivity of the JA pathway through silicon, could indicate that along with increased physical defenses the volatiles also helped deter the mobile piercing sucking herbivores (Pare & Tumlinson 1999, Reynolds et al 2016).…”
Section: Discussionmentioning
confidence: 99%